Controle mecânico de plantas daninhas na cultura da soja em sistema de semeadura direta - Arns, Kurt (2007)
Aiming to study the effect of an articulated cultivator on the mechanical control of weeds in the soybean crop cultivated under the notillage system, a study was carried out at the experimental field of Fundação Centro de Experimentação e Pesquisa Fecotrigo Fundacep Fecotrigo, in Cruz Alta county, Rio Grande do Sul state, Brazil. The experimental design used was of randomized blocks, with treatments arranged in sub-divided plots and with four replications. Different weeding dates (main plots) were used as treatments in this study and were performed at 7, 14, 21, 28 and 30 days after emergence (DAE) of the soybean crop, and the sequential weedings at 14 and 30 DAE. Two other treatments were done, one with total control of weed plants (manual pulling) and another without control during the entire soybean cycle and presence and absence of weeds in the row. The effects of the treatments were evaluated through weed density, dry matter, cutting height, ability to re-sprout, plant height, yield components and soybean grain yield. Results were evaluated through the analysis of variance and the means compared using the Tukey test. This study put into evidence that the interference of weeds reduce grain yield in the soybean crop cultivated under the no-tillage system. The population density of remaining weeds after the application of the treatments is higher in the row than in the area between the rows. The presence of weeds in the row has a negative interference in the soybean crop, in the following decreasing order: legumes plant-1 > branches plant-1 > legumes stem-1 and grain dry matter stem-1. Interference of row weed plants in the soybean crop reduce grain yield. There is no effect of weed plants mechanical control dates on soybean cultivated under the no-tillage system